2011
DOI: 10.1002/pssb.201100191
|View full text |Cite
|
Sign up to set email alerts
|

Density of states deduced from ESR measurements on low‐dimensional nanostructures; benchmarks to identify the ESR signals of graphene and SWCNTs

Abstract: Electron spin resonance (ESR) spectroscopy is an important tool to characterize the ground state of conduction electrons and to measure their spin-relaxation times. Observing ESR of the itinerant electrons is thus of great importance in graphene and in single-wall carbon nanotubes (SWCNTs). Often, the identification of CESR signal is based on two facts: the apparent asymmetry of the ESR signal (known as a Dysonian lineshape) and on the temperature independence of the ESR signal intensity. We argue that these a… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
19
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
4
1
1

Relationship

3
3

Authors

Journals

citations
Cited by 17 publications
(19 citation statements)
references
References 25 publications
0
19
0
Order By: Relevance
“…[13] Hence, in regions in which O 2 and graphene electron spins are separated by less than % 1.1 nm, an ESR signal would not be observed in our experiments. This is because ESR can only detect regions in which the line width is sufficiently narrow, as the signal amplitude is inversely proportional to the square of the line width.…”
Section: Electron Spin Resonance Spectroscopy Studiesmentioning
confidence: 63%
See 2 more Smart Citations
“…[13] Hence, in regions in which O 2 and graphene electron spins are separated by less than % 1.1 nm, an ESR signal would not be observed in our experiments. This is because ESR can only detect regions in which the line width is sufficiently narrow, as the signal amplitude is inversely proportional to the square of the line width.…”
Section: Electron Spin Resonance Spectroscopy Studiesmentioning
confidence: 63%
“…This is because ESR can only detect regions in which the line width is sufficiently narrow, as the signal amplitude is inversely proportional to the square of the line width. [13] Hence, in regions in which O 2 and graphene electron spins are separated by less than % 1.1 nm, an ESR signal would not be observed in our experiments. This is the origin of the loss of the ESR signal upon O 2 exposure.…”
Section: Electron Spin Resonance Spectroscopy Studiesmentioning
confidence: 63%
See 1 more Smart Citation
“…Although all three spectra reveal the presence of paramagnetic species, it can be concluded that blue-TiO 2 NWs provide the strongest EPR-detectable feature (blue trace). In particular, as discussed in details in [53], the strong EPR signal observed for blue-TiO 2 NWs corresponds to a powder EPR spectrum of the surfacelocated Ti 3+ paramagnetic centers. We demonstrate our general approach to study the interface using the blue-TiO 2 NWs due to the large Ti 3+ surface defect concentration and the corresponding large EPR signal intensity.…”
Section: Quantification Of the Charge Transfer At The Mapbi 3 /Blue-tmentioning
confidence: 83%
“…We demonstrate our general approach to study the interface using the blue-TiO 2 NWs due to the large Ti 3+ surface defect concentration and the corresponding large EPR signal intensity. For distorted (tetragonally-elongated) octahedral sites this signal can be fitted with a uniaxial powder distribution having two g-factor components: parallel (g P =1.94) and perpendicular (g ⊥ =1.97) ( [53] and references therein). The temperature dependence of the EPR signal intensity confirmed the Curie-type behaviour for these Ti 3+ -related paramagnetic centers in blue-TiO 2 NWs (see supplementary material, figure S4.).…”
Section: Quantification Of the Charge Transfer At The Mapbi 3 /Blue-tmentioning
confidence: 99%